Penalaran Hukum (Istinbāṭ) Walimatul ‘Ursy dalam Fikih Syafi’iyah dan Relevansinya terhadap Kompilasi Hukum Islam di Indonesia - Heri Firmansyah; Mukhlis Tri Mulya Marpaung (Albayan Journal of Islam and Muslim Societies, 2025)
Walīmat al-ʿurs constitutes an important socio-religious practice in Islamic marriage, particularly within Muslim societies that adhere to the Shāfiʿī school of law. This article examines the legal reasoning (istinbāṭ) employed by Shāfiʿī jurists in determining the legal status of walīmat al-ʿurs and analyzes its relevance to Indonesia’s Compilation of Islamic Law (Kompilasi Hukum Islam/KHI). Employing a normative legal research method with conceptual and comparative approaches, this study analyzes classical Shāfiʿī legal texts alongside statutory Islamic family law in Indonesia. The findings demonstrate that Shāfiʿī jurists derive the ruling of walīmat al-ʿurs through an integrative mode of legal reasoning that combines textual commands of the Prophet, contextual indicators (qarāʾin), and functional considerations of marriage publicity (iʿlān al-nikāḥ), resulting in its classification as sunnah muʾakkadah. Meanwhile, the absence of explicit regulation on walīmat al-ʿurs in the KHI reflects a legislative choice to prioritize administrative and juridical aspects of marriage over ritual-social practices. This study argues that walīmat al-ʿurs remains epistemologically, normatively, and functionally relevant to the KHI as a form of living Islamic law that complements codified legal norms. The article contributes to Islamic legal scholarship by highlighting the continued relevance of classical Shāfiʿī legal reasoning in understanding and evaluating contemporary Islamic family law in Indonesia.